विश्व राजनीतिमा वैज्ञानिक समाजवादी चिन्तनको विकास The Development of Scientific Socialist Thought in World Politics - मैनाली Mainali गोविन्द प्रसाद Govinda Prasad (Interdisciplinary Journal of Management and Social Sciences, 2024)
This article examines the development of scientific socialist thought in world politics. Key milestones considered include the formation of the Communist League, the publication of the Communist Manifesto, the establishment of the First International, the Paris Commune, the Second International, the October Socialist Revolution, the Third International, and the Cominform. Scientific socialist thought began with the publication of the Communist Manifesto by Marx and Engels in 1848 and developed gradually over time. This evolution is marked by a series of significant historical events. The study traces the formation of the Communist League, the creation and dissemination of the Communist Manifesto, the establishment of the First International under Marx’s leadership, the Paris Commune revolution by workers and the proletariat, the formation of the Second International under Engels’ guidance, Lenin’s leadership in the Russian Socialist Revolution and the formation of the Third International, and the establishment of the Cominform under Stalin’s leadership. The article uses an inductive method to explore these developments and aims to illuminate the progression of scientific socialist thought in world politics.